2012
DOI: 10.1063/1.4759455
|View full text |Cite
|
Sign up to set email alerts
|

Time growth rate and field profiles of hybrid modes excited by a relativistic elliptical electron beam in an elliptical metallic waveguide with dielectric rod

Abstract: The dispersion relation of guided electromagnetic waves propagating in an elliptical metallic waveguide with a dielectric rod driven by relativistic elliptical electron beam (REEB) is investigated. The electric field profiles and the growth rates of the waves are numerically calculated by using Mathieu functions. The effects of relative permittivity constant of dielectric rod, accelerating voltage, and current density of REEB on the growth rate are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…30,37 Thus, the solutions of no-beam dispersion relation give the expected operating frequency of this configuration. Equation (29) presents the beam modes. These two modes are coupled via the interaction term on the right-hand side of Eq.…”
Section: Dispersion Equation and Growth Rate Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,37 Thus, the solutions of no-beam dispersion relation give the expected operating frequency of this configuration. Equation (29) presents the beam modes. These two modes are coupled via the interaction term on the right-hand side of Eq.…”
Section: Dispersion Equation and Growth Rate Discussionmentioning
confidence: 99%
“…In this figure, the operating frequency is determined from the synchronism of Eqs. (28) and (29). Here, normalized operating frequency is x 0 a 1 /c ¼ 15.2392.…”
Section: Simulation Of Dispersion Characteristics and Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new kind of high-power THz source, called electron beam-plasma system (EBPS) has attracted wide attention [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This THz source does not have a damage threshold as the plasma is in a highly ionized state.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have successfully observed powerful THz radiation from EBPS in a large magnetic confinement plasma device [16][17][18]. Meanwhile, various related THz radiation mechanisms have also been investigated [19][20][21][22][23][24][25][26][27][28][29]. It can be found that all the previous studies adopt linear schemes considering a single beam or two counterstreaming beams passing through a plasma column.…”
Section: Introductionmentioning
confidence: 99%